USE OF OPERATIONAL MECHANISMS OF MNEMONIC ABILITIES BY SUBJECTS WHEN MEMORIZING COMPLEX UNCOMPLICABLE MATERIAL - S. A. Dyupina (Вестник университета)
The results of studying the operational mechanisms of mnemonic abilities of subjects of different ages when memorizing complicated non-verbal meaningless material have been presented. The study was carried out by means of the deployment method of mnemonic activity by L. V. Cheremoshkina. In the group of first-graders, information processing was carried out at the perceptual and perceptual-shaped levels. The operational mechanisms of grouping, strong point, association were the leading ones. In a group of students, information was processed primarily at a intellectual level. The operational mechanisms of schematization and structuring were the leading ones. In the group of subjects 35–40 years of age, information processing was carried out at a figurative-mental level. Memorization was carried out thanks to the operational mechanisms of the grouping, strong point, schematization. In general, in the sample of the subjects examined by us, when memorizing complicated non-verbal senseless material, the operational mechanisms of grouping and strong point prevailed.